Key concepts in psychology - Winstanley, Julie (Basingstoke [England] ; New York : Palgrave Macmillan, 2006)
"Key Concepts in Psychology provides an accessible and comprehensive guide to the major terms and concepts encountered in psychology. Each entry is placed alphabetically for ease of use and gives a clear definition followed by relevant examples, links to further reading, and website references that point to additional resources for study."--BOOK JACKET.
The key concepts A-Z -- Key statistical concepts -- Key theorists -- Key theories -- Key psychological approaches -- Key research concepts -- Key psychological acronyms -- List of phobias -- Key psychological weblinks.
Includes index.
Includes bibliographical references and index.
Keywords: Psychology -- Dictionaries; Psychology -- Dictionary -- English